Domain I: the hidden face of antiphospholipid syndrome. (October 2014) - Pericleous, C; Rahman, A
IgG antiphospholipid antibodies (aPL) against β2 -glycoprotein I (β2 GPI) can target any of its five domains; however, aPL against the N-terminal domain (anti-DI, aDI) are considered the most clinically relevant in the antiphospholipid syndrome (APS). Circulating levels of aDI are elevated in patients with APS compared with disease and healthy controls, and crucially aDI are prothrombotic in in vivo and in vitro models. In addition, human recombinant DI has been shown to abrogate aPL-induced thrombosis in vivo. Therefore, although the potential of utilizing DI for management of APS is not yet fully defined, there is promise that DI could prove valuable both as a diagnostic and therapeutic tool.